Sequencing individual genomes with recurrent genomic disorder deletions: an approach to characterize genes for autosomal recessive rare disease traits - Yuan, Bo; Schulze, Katharina V.; Assia Batzir, Nurit; Sinson, Jefferson; Dai, Hongzheng; Zhu, Wenmiao; Bocanegra, Francia; Fong, Chin-To; Holder, Jimmy; Nguyen, Joanne; Schaaf, Christian P.; Yang, Yaping; et al. (Genome medicine, 2022)
In medical genetics, discovery and characterization of disease trait contributory genes and alleles depends on genetic reasoning, study design, and patient ascertainment; we suggest a segmental haploid genetics approach to enhance gene discovery and molecular diagnostics.